Evaluasi Kelayakan Dan Penggambaran Usaha Budidaya Ikan Nila Merah Keramba Jaring Apung Di Kampung Keramba, Waduk Gajah Mungkur, Wonogiri - Alazhari, Burhanudin, Indah Pratiwi ST.,MT (2017)
The fishery industry is an organized activity related to the management and utilization of fish resources and the environment, ranging from pre-production, production to marketing are carried out within one business fishing industry. Gajah Mungkur Wonogiri has the potential for the cultivation of freshwater that is floating cages. The purpose of this study is to measure the feasibility evaluaton of using a financial analysis and economics through some of the eligibility criteria of business, namely Payback Period, Net Present Value, Internal Rate of Return, ProfitabilityIndex, Break Eventand depictions of aspects of the business using the business Model Canvas (BMC). The results of a financial analysis floating cages red tilapia fish in the study area seen from the calculation of the Payback Period that is 6 months 7 days, an Internal Rate of Return of 84% for 2 years, the Net Present Value for 2 years has a value of Rp 82,943,219.00, Profitability Index for 2 years ie amounted to 5.155, Break Event Point on the amount of sales of 4.280 kg in the 24-month year-to-2 or in the number of admissions of Rp 109,217,040.00, shows that the business is feasible and has a huge advantage. Aspects of the market determines the value dapam increase profit from the work done, while determining the environmental aspects in the process of quality control environment, especially the water reservoir as the main means of supporting business continuity floating net cages of tilapia merah.Dalam depiction of aspects of the business using the Business Model Canvas (BMC) for the cultivation of floating net cage red tilapia fish in the study area there are nine components. Ninth such components have their respective roles in this business activity. Keywords: Keramba cage, Red Tilapia Fish, Feasibility Evaluation Analysis, BMC